ANALISIS EFEKTIVITAS PENGELOLAAN KEUANGAN DAN KINERJA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KEEROM - Devina Petrina; Mollet, Julius Ary; Fallah, Syaikhul (Universitas Cenderawasih, 2023)
The effectiveness of government financial management is one of the most important things in setting the priorities of a country's social and economic development. To minimize weaknesses in public services, the government began to increase the use of technology in its services. One of the programs is in the form of one-stop integrated services. This study aims to analyze, test and measure the performance of the Investment Office and One-Stop Integrated Services using the Balance Scorecard Method. This type of research is quantitative descriptive research. The sample in this study was 40 employees and 60 community respondents who made permits at the Investment Office and One-Stop Integrated Services of Keerom Regency, which were taken using a simple random sampling technique. The data collection method is carried out through the distribution of questionnaires, observations, and documentation. The data that has been collected is then tested for validity through validity tests and reliability tests. The results of the study using the balance scorecard method showed that the Effectiveness of Financial Management in DPMPTSP Keerom Regency based on the financial perspective showed